1980
DOI: 10.1149/1.2129690
|View full text |Cite|
|
Sign up to set email alerts
|

Formation Mechanism of Porous Silicon Layer by Anodization in  HF  Solution

Abstract: The mechanism of formation of porous silicon layer (PSL) has been studied according to the following experimental results. PSL is formed by the local dissolution of silicon which occurs only at the base of the pores. The HF concentration of the electrolyte in the pores of PSL is constant during anodization and the anodic reaction in the pores proceeds uniformly in the thickness direction. The dissolution of silicon in the pores is the results of the divalent and the tetravalent reactions of silicon with HF ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(56 citation statements)
references
References 12 publications
2
54
0
Order By: Relevance
“…It was found that the pores at the surface usually have smaller diameter than those in the bulk of PSi (Figure 76h). 40,49,415,444 Such an increase in pore diameter from the surface to bulk is due to the transition from pore initiation to steady growth. The thickness of this transition layer is related to the size of pores; the smaller the pores are, the thinner is the surface transition layer.…”
Section: Influence Of Anodization Parameters On Microstructure Of Psimentioning
confidence: 99%
“…It was found that the pores at the surface usually have smaller diameter than those in the bulk of PSi (Figure 76h). 40,49,415,444 Such an increase in pore diameter from the surface to bulk is due to the transition from pore initiation to steady growth. The thickness of this transition layer is related to the size of pores; the smaller the pores are, the thinner is the surface transition layer.…”
Section: Influence Of Anodization Parameters On Microstructure Of Psimentioning
confidence: 99%
“…doped-Si, Al). [17][18][19] In this scheme, modulation of the anodic current through a substrate immersed in an acidic solution allows pores to be etched with size tunable from nm to µm. 19-21 materials, requires a complex and multi-step fabrication and generally yields layers with low refractive index (RI) contrast.…”
mentioning
confidence: 99%
“…Watanabe and Sakai were probably therefore the first to create highly microporous silicon, albeit without realizing it (Watanabe and Sakai 1971). Other workers who conducted early studies on the properties of layers anodized in p-wafers using highly concentrated HF included Unagami (1980) and Koshida et al (1985) who correctly referred to a "microporous structure" (Koshida et al 1986). The 1988 review of Bomchil et al (1988) clarified the trends in poresize distribution with anodization parameters for a range of mesoporous layers.…”
Section: Micropores In Siliconmentioning
confidence: 99%